Learning from terrorist mass casualty incidents: a global survey. (February 2022) - Tallach, Rosel; Einav, Sharon; Brohi, Karim; Abayajeewa, Kirthi; Abback, Paer-Sellim; Aylwin, Chris; Batrick, Nicola; Boutonnet, Mathieu; Cheatham, Michael; Cook, Fabrice; Curac, Sonja; Davidson, Stephanie; et al.
Abstract: Background: Reports published directly after terrorist mass casualty incidents frequently fail to capture difficulties that may have been encountered. An anonymised consensus-based platform may enable discussion and collaboration on the challenges faced. Our aim was to identify where to focus improvement for future responses. Methods: We conducted a mixed methods study by email of clinicians' experiences of leading during terrorist mass casualty incidents. An initial survey identified features that worked well, or failed to, during terrorist mass casualty incidents plus ongoing challenges and changes that were implemented as a result. A follow-up, quantitative survey measured agreement between responses within each of the themes using a Likert scale. Results: Thirty-three participants responded from 22 hospitals that had received casualties from a terrorist incident, representing 17 cities in low-middle, middle and high income countries. The first survey identified themes of sufficient (sometimes abundant) human resource, although coordination of staff was a challenge. Difficulties highlighted were communication, security, and management of blast injuries. The most frequently implemented changes were education on specific injuries, revising future plans and preparatory exercises. Persisting challenges were lack of time allocated to training and psychological well-being. The follow-up survey recorded highest agreement amongst correspondents on the need for re-triage at hospital (90% agreement), coordination roles (85% agreement), flexibility (100% agreement), and large-scale exercises (95% agreement). Conclusion: This survey collates international experience gained from clinicians managing terrorist mass casualty incidents. The organisation of human response, rather than consumption of physical supplies, emerged as the main finding. NHSH Clinical Effectiveness Unit project registration number: 2020/21–036.